2021
DOI: 10.4037/ccn2021551
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Stimulation in an Intensive Care Unit: A Qualitative Evaluation of Barriers to and Facilitators of Implementation

Abstract: Background Delirium in the intensive care unit is associated with poor patient outcomes. Recent studies support nonpharmacological therapy, including cognitive stimulation, to address delirium. Understanding barriers to cognitive stimulation implemented by nurses during clinical care is essential to translating evidence into practice. Objective To use qualitative methods through a structured quality improvement project to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…57 However, data on early cognitive exercise and interventions to prevent cognitive impairment in critically ill cardiac patients is limited. In one qualitative study, Parker et al 58 demonstrated many barriers to implementing early combined cognitive stimulation and goal-directed mobility performed by nurses in the medical ICU. In this study, nurses administered a workbook of evidence-based tasks to the patients at least once per shift, with tasks focused on math, alertness, problem-solving, and language.…”
Section: Preventionmentioning
confidence: 99%
“…57 However, data on early cognitive exercise and interventions to prevent cognitive impairment in critically ill cardiac patients is limited. In one qualitative study, Parker et al 58 demonstrated many barriers to implementing early combined cognitive stimulation and goal-directed mobility performed by nurses in the medical ICU. In this study, nurses administered a workbook of evidence-based tasks to the patients at least once per shift, with tasks focused on math, alertness, problem-solving, and language.…”
Section: Preventionmentioning
confidence: 99%